Madhyaprācye Hāphejjī Hujura - Phārūka, Ākhatāra, 1935- (Hijabullāha Prakāśanī, 1983)
Narrative of the visit of Hāphejjī Hujura, Bengalee politicoreligious leader, to Saudi Arabia, Iran, and Iraq; by a member of his entourage.